Agriman Agventures. Secrets of the soil: Ag-tivities - Programa de Acción Climática y Sostenibilidad Agropecuaria (PACSA) (W.H.Y. Farm, 2023)
Two support tools are presented for addressing awareness topics related to preserving natural resources. Each of the materials is directed respectively at children aged 4 to 7 and 8 to 12.